Proton MR spectroscopy of lesion evolution in multiple sclerosis: Steady‐state metabolism and its relationship to conventional imaging. Issue 8 (19th May 2017) - Kirov, Ivan I.; Liu, Shu; Tal, Assaf; Wu, William E.; Davitz, Matthew S.; Babb, James S.; Rusinek, Henry; Herbert, Joseph; Gonen, Oded
Abstract: Although MRI assessment of white matter lesions is essential for the clinical management of multiple sclerosis, the processes leading to the formation of lesions and underlying their subsequent MRI appearance are incompletely understood. We used proton MR spectroscopy to study the evolution of N ‐acetyl‐aspartate (NAA), creatine (Cr), choline (Cho), and myo ‐inositol (mI) in pre‐lesional tissue, persistent and transient new lesions, as well as in chronic lesions, and related the results to quantitative MRI measures of T1‐hypointensity and T2‐volume. Within 10 patients with relapsing‐remitting course, there were 180 regions‐of‐interest consisting of up to seven semi‐annual follow‐ups of normal‐appearing white matter (NAWM, n = 10), pre‐lesional tissue giving rise to acute lesions which resolved ( n = 3) or persisted ( n = 3), and of moderately ( n = 9) and severely hypointense ( n = 6) chronic lesions. Compared with NAWM, pre‐lesional tissue had higher Cr and Cho, while compared with lesions, pre‐lesional tissue had higher NAA. Resolving acute lesions showed similar NAA levels pre‐ and post‐formation, suggesting no long‐term axonal damage. In chronic lesions, there was an increase in mI, suggesting accumulating astrogliosis. Lesion volume was a better predictor of axonal health than T1‐hypointensity, with lesions larger than 1.5 cm 3 uniformly exhibiting very low (<4.5 millimolar) NAA concentrations. A positive correlation between longitudinal changes in Cho and in lesion volume in moderately hypointense lesions implied that lesion size is mediated by chronic inflammation. These and other results are integrated in a discussion on the steady‐state metabolism of lesion evolution in multiple sclerosis, viewed in the context of conventional MRI measures. Hum Brain Mapp 38:4047–4063, 2017 . © 2017 Wiley Periodicals, Inc.